Hay-wells syndrome with selective immunoglobulin a deficiency - Bhupathi Sharanya; Rajendran Narayanan; Manobalan Karunanandhan (Wolters Kluwer Medknow Publications, 2020)
Hay-Wells syndrome or ankyloblepharon-ectodermal dysplasia-cleft lip/palate (AEC) syndrome is a rare form of ectodermal dysplasia. It is an autosomal dominant disorder with various congenital abnormalities involving the skin, hair, teeth, nails, and sweat glands. We report a case of a 7-year-old boy who presented with scaly lesions all over the body that was noticed since birth. The child had scalp erosions and fusion of the eyelids at birth. The child even had patchy scaring alopecia with scaling over the vertex, decreased sweating, and poor formation of nails since birth. We also noted frontal bossing in the child. Epiphora and sparse eye lashes were noted in both eyes. Ear-nose-throat examination revealed rudimentary bifid uvula, aural polyp in the right ear, and abnormal dentition. In view of these clinical signs and symptoms, we arrived at a clinical diagnosis of ankyloblepharon-ectodermal dysplasia-cleft palate (AEC). Due to recurrent scalp pyodermas and seborrheic dermatitis in infancy, the child was suspected and confirmed to have selective immunoglobulin A (IgA) deficiency. We report this case in view of its rare association, i.e., AEC, with selective IgA deficiency.